Representasi Peran Tokoh Abuela Sebagai Nenek Dalam Film Animasi Encanto - Arelle Nathania Sahulata; Dimas Satrio Wijaksono (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Encanto is a computer-animated family film with musical, comedy, and fantasy genres. The Encanto film won an Academy Award (Oscar) for Best Animated Film in 2022. As a mass communication medium, the Encanto film represents a unique reality where women play an important societal role. In the film Encanto, Abuela, the grandmother of the Madrigal family, plays an essential role in the existence of the Madrigal family and the community of Encanto. This reality generally differs from the reality of life, where men dominate essential societal roles. This study aims to describe the role of Abuela represented in the film Encanto at three levels of John Fiske's semiotics: the level of reality, the level of representation, and the level of ideology. The research used a qualitative method with an analysis of  John Fiske's semiotic theory based on constructivist paradigm. After conducting research, the researcher found that Abuela's roles in the film Encanto include family historian, teacher, head of the Madrigal family, and head of the community of Encanto. That role is represented by authoritative, firm, weak, and prone to wounds (melancholy) characteristics. In addition, a matriarch ideology was found as the basis of Abuela's role among the people of Encanto.